2017
DOI: 10.1021/acs.energyfuels.7b01754
|View full text |Cite
|
Sign up to set email alerts
|

Organic Geochemistry and Petrology of Mudrocks from the Upper Carboniferous Batamayineishan Formation, Wulungu Area, Junggar Basin, China: Implications for Petroleum Exploration

Abstract: The hydrocarbon generation potential of the Carboniferous Batamayineishan mudrocks has been overlooked for a long time. In this study, organic petrology and geochemistry were used to determine the sedimentary environments, organic matter (OM) type, and organic maturity of the Carboniferous Batamayineishan source rocks, collected from outcrops, Wulungu area, Junggar Basin, China. The maceral composition of the studied samples is dominated by vitrinite and inertinite, ranging from 40 vol % to 100 vol % and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Kerogen type index (TI) was calculated by utilizing the method proposed by Cao (1985), which has been used to evaluate kerogen types of lacustrine shale (Tao et al 2012;Luo et al 2017). The maceral of kerogen is composed of sapropelinite, exinite, vitrinite, and inertinite.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kerogen type index (TI) was calculated by utilizing the method proposed by Cao (1985), which has been used to evaluate kerogen types of lacustrine shale (Tao et al 2012;Luo et al 2017). The maceral of kerogen is composed of sapropelinite, exinite, vitrinite, and inertinite.…”
Section: Methodsmentioning
confidence: 99%
“…5a, b, c, and d) and a bright-yellow color under the fluorescent microscope. The hydrogen-rich organic matters are the degradation products of aquatic organisms and algae under strong reducing conditions and have a significant petroleum generation potential (Burgess 1974;Rahman and Kinghorn 1995;Luo et al 2017). Well-preserved elliptic alginite ranging from tens to hundreds of microns in size is found in the sapropelinite and exhibits a yellow-brown color under transmitted light (Fig.…”
Section: Organic Matter Typementioning
confidence: 99%
See 1 more Smart Citation
“…The exploration and commercial development of shale oil have expanded rapidly in many countries in recent years. In 2019, the daily crude oil production in the USA, for example, was 12.26 MMb d –1 , of which 65.17% or 7.99 MMb d –1 was produced from shale sequences . Large shale oil resources have recently been discovered in Chinese lacustrine basins with organic-rich shale and strongly heterogeneous sequences, such as in the Ordos, Songliao, Junggar, and Bohai Bay basins. The Middle Permian Lucaogou Formation (P 2 l) in the Jimsar Sag of the Junggar Basin, NW China, is one of the main areas of lacustrine shale oil exploration and exploitation in China. Oil production has shown that the Lucaogou Formation has upper and lower sweet spots, both characterized by marked heterogeneity and frequent interbedded shale and tight reservoirs. , The current exploration target is focused on the tight oil reservoirs of the formation because whether oil in shale is also a potential exploration target remains uncertain. A method to determine whether the oil is produced from shale in the Lucaogou Formation needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The search for reliable thermal maturity indicators to determine the maturity of oil and source rock is an important objective in petroleum geochemistry, especially for shale resource where most biomarkers are unreliable. Polyaromatic hydrocarbons (PAHs) and organosulfur compounds (OSCs) formed by complex thermal bond-breaking and dehydrogenation reactions from biogenic precursors during diagenetic and catagenetic processes or a pyrolytic process are widely distributed in highly matured oils, source rocks and coals and their relative abundances and structural isomer distributions can serve as reliable maturity assessment tools. Generally, these maturity parameters rely either on the degree of alkylation of a given parent compound or a shift in the isomer distribution of homologues toward thermally more stable isomers. It has been assumed that significant quantities of alkyl aromatic hydrocarbons in sediments may be derived by alkylation of parent aromatic hydrocarbons , and the degree of alkylation may reflect the level of maturity.…”
Section: Introductionmentioning
confidence: 99%